PERAN BRAND IMAGE MEMEDIASI PENGARUH SOCIAL MEDIA TERHADAP KEPUTUSAN PEMBELIAN PADA LAZADA - Nurani, Ni Wayan Shanti Dwi; Ardani, I Gusti Agung Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.11.TAHUN.2023DO - 10.24843/EEB.2023.v12.i11.p08, 2023)
The development of technology and the internet has a great impact on business changes. The e-commerce platform is the main driver of the growth of the digital economy in Indonesia. Lazada is one of the e-commerce sites in Indonesia with a low level top of mind share, market share, and commitment share compared to its competitors according to Top Brand Index data. This study aims to examine and explain the role of brand image mediating social media on purchasing decisions at Lazada. This research was conducted in Denpasar City with the number of samples taken as many as 100 respondents with a questionnaire tool. The sample was determined using a non-probability sampling model with a purposive sampling technique. The data analysis technique used is PLS-based SEM analysis. The results of this study indicate that all hypotheses are accepted. Social media has a significant positive effect on purchasing decisions at Lazada. Social media has a significant positive effect on Brand Image at Lazada. Brand Image has a positive and significant effect on purchasing decisions at Lazada. Brand Image Mediates the influence of Social media on purchasing decisions on Lazada.